Education On the Contents of My Plate to Mothers in an Effort to Prevent Stunting at Posyandu Melati 7 Kel. Bandar Selamat - Harahap, Reni Agustina; A'ini, Sharifah; Nst, Sopiah Widi Rahma (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT One of them is the problem of malnutrition, if food consumption is not fulfilled then the risk of nutritional problems arises, one of which decreases. Mother's nutritional knowledge influences diet and the quality of food provided. The higher the knowledge of nutrition, the more it affects the attitude and behavior of food consumption. One of the efforts to achieve a balanced diet is to use the "Fill My Plate" portion of food. The purpose of this training is to increase knowledge about the concept of my plate and stunt. The operating method applied is counseling with the lecture method with the help of brochures / posters containing explanations of the contents of the plate and the concept of squatting. The results of this training are visible on the before and after tests. The mother's knowledge of the contents of the dishes and the lethargy of small children increases. In conclusion, mothers who have young children understand the importance of providing nutrition to young children to prevent their growth in the first place. Keywords: Education, Fill My Plate, Stunting, Toddler